Islamic Clicktivism: Internet, Democracy and Contemporary Islamist Activism in Surakarta - Ahyar, Muzayyin (Studia Islamika, 2017)
Since the collapse of the New Order regime, social development has led Indonesia to become a more democratic and modern than any other Muslim majority countries. The development of democracy in Indonesia has also seen the proliferation of modern Islamist activism online. This form of cyber activism, named here as Islamic “clicktivism,” has a discursive function. This paper examines how the proliferation of a cyber Islamist movement can be related to ongoing democratization in Indonesia. It was found that Islamic clicktivism has emerged in the process of democratization, modernization and globalization. Clicktivism encourages members of Islamist groups to adopt the principles and logic of the pillars of democracy, and to perpetuate their struggle and promote their existence during the development of democracy in Indonesia. Through their clicktivism, they bring the discursive voices of Islamism democratically to national issues in the common interest of Indonesians.DOI: 10.15408/sdi.v24i3.4859